ChanFAD: A Functional Annotation Database for Ion Channels - Castro, Elizabeth V.; Shepherd, John W.; Guggenheim, Ryan S.; Sengvoravong, Manimone; Hall, Bailey C.; Chappell, McKenzie K.; Hearn, Jessica A.; Caraccio, Olivia N.; Bissman, Cora; Lantow, Sydney; Buehner, Damian; Costlow, Harry R.; et al. (Frontiers in Bioinformatics, 2022)
Ion channels are integral membrane protein complexes critical for regulation of membrane potential, cell volume, and other signaling events. As complex molecular assemblies with many interacting partners, ion channels have multiple structural and functional domains. While channel sequence and functional data are readily available across multiple online resources, there is an unmet need for functional annotation directly relating primary sequence information, 2D interactions, and three-dimensional protein structure. To this end, we present ChanFAD (Channel Functional Annotation Database), to provide the research community with a centralized resource for ion channel structure and functional data. ChanFAD provides functional annotation of PDB structures built on the National Center for Biotechnology Information’s iCn3D structure viewing tool while providing additional information such as primary sequence, organism, and relevant links to other databases. Here we provide a brief tour of ChanFAD functionality while showing example use cases involving drug-channel interactions and structural changes based on mutation. ChanFAD is freely available and can be accessed at https://www.chanfad.org/.